2010
DOI: 10.1096/fj.09-147033
|View full text |Cite
|
Sign up to set email alerts
|

The midregion, nuclear localization sequence, and C terminus of PTHrP regulate skeletal development, hematopoiesis, and survival in mice

Abstract: The functions of parathyroid hormone-related protein (PTHrP) on morphogenesis, cell proliferation, apoptosis, and calcium homeostasis have been attributed to its N terminus. Evidence suggests that many of these effects are not mediated by the N terminus but by the midregion, a nuclear localization sequence (NLS), and C terminus of the protein. A knock-in mouse lacking the midregion, NLS, and C terminus of PTHrP (Pthrp(Delta/Delta)) was developed. Pthrp(Delta/Delta) mice had craniofacial dysplasia, chondrodyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…Other in vivo genetic mouse models have also indicated that the midregion and C-terminus of PTHrP are functional. (8) Cell cycle regulation is conducted by sequential activation of a family of serine-threonine kinases called cycle-dependent kinases (CDKs). Tight CDK regulation involves cyclin-dependent kinase inhibitors (CKIs), which ensure the correct timing of CDK activation in different phases of the cell cycle.…”
mentioning
confidence: 99%
“…Other in vivo genetic mouse models have also indicated that the midregion and C-terminus of PTHrP are functional. (8) Cell cycle regulation is conducted by sequential activation of a family of serine-threonine kinases called cycle-dependent kinases (CDKs). Tight CDK regulation involves cyclin-dependent kinase inhibitors (CKIs), which ensure the correct timing of CDK activation in different phases of the cell cycle.…”
mentioning
confidence: 99%
“…Specifically, disruption of cell-cell adhesion function of Armadillo results in construction defects of the axonal scaffold (Loureiro and Peifer, 1998). Interestingly, a recent study suggested that PLA 2 a regulates the Wnt/b-catenin pathway (Han et al, 2008), which is implicated in neurogenesis, CNS morphogenesis, hirsutism, sweat gland morphology, short tendons, and kyphosis (Toribio et al, 2010;Haara et al, 2011;Joksimovic and Awatramani, 2014;Zhang et al, 2014). In this pathway, b-catenins transduce Wnt signals during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…PTHrp gene knockout mice present dyschondroplasia, hump, and mammary dysplasia (Toribio et al, 2010). PTHrP induces osteoclast formation, and decreases osteoblast function in diabetes-related osteopenia patients (Lozano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%